Practice of total quality management model in the "One Syndrome and One Product" specialized nursing demonstration wards (全面质量管理模式在“一证一品”专科护理示范病房管理中的实践) - LI Jing (李静); LI Yueru (李月茹); CAO Hongjing (曹红京); LI Ning (李宁); TIAN Zhijun (田志军) (中西医结合护理)
Hospital has launched the construction project of the "One Syndrome and One Product" specialized nursing demonstration wards and established a service band of Traditional Chinese Medicine nursing focusing on elderly care. The total quality management model has been built and put into practice, in order to improve the quality of specialized nursing and enhance the comprehensive ability of nurses. Standard, specialized and homogenized nursing service was provided to improve the patient satisfaction. (医院开展“一证一品”专科护理示范病房建设, 创立突出老年特色的中医护理服务品牌, 构建及实施全面质量管理(TQM)模式, 进一步提高专科护理服务水平, 提升护理人员的综合护理质量, 使患者获得规范化、专业化、同质化的护理服务, 提升患者满意度。)